СREATING A TRAINING PROGRAMME FOR COMMUNITY-BASED PARALEGALS: ACTION RESEARCH - Yeroshenko, Kateryna; Semigina, Tetyana (Social work and education, 2017)
The paper presents the dynamic process of developing an educational course for paralegals undertaken with the support of the ‘Human Rights and Justice Program Initiative’ (run by the International Renaissance Foundation). Based on the approach of action research, the course design was changed from the initial experts’ vision, based on the desk-review analysis of the international practices of paralegal studies and following the suggestions of practitioners who took part in the training of trainers. The study highlights a range of challenges in designing an educational course for individuals with a brand new role in society. In particular, there was no holistic understanding of the idea of paralegalism among trainers in local communities. Thus, the vision of who can become a paralegal, and the criteria for selecting people from local communities to take part in the educational course, were based on results of a trainer’s discussion (as well as on the compilation of expert analysis and ideas adopted from international experience.The study demonstrates how to design the training for trainers, while trainers-participants have an opportunity to show their skills and understanding of the received information. Such a design can be used for teaching complex or brand new concepts that require additional discussion. Parts of this course can also be applied as separate training for community activists, since the course is aimed to educate on the use instruments of community facilitation and service integration.